A numerical eigenmode analysis of the progressive buckling of thin-walled tubes - Fuggle, Timothy Mark (Department of Mechanical Engineering, 2024)
[page 76 missing]Structural impact is concerned with the behaviour of structures subject to static and dynamic loads which produce inelastic deformations. This field is of particular interest for the crash-worthiness design of aeroplanes, motor cars, buses, trains, ships and marine structures, where the survivability of passengers is at risk, as well as for the energy absorbing characteristics of various other components such as the petrochemical industry for safety devices. Progressive buckling of thin-walled tubes has already been used very successfully to absorb the kinetic energy during impact between motor vehicles, trains, etc. A great deal of research has been performed in the field of energy absorption devices and in particular for thin-walled square and cylindrical tubes being axially crushed. Many rigorous and time-consuming experimental models have been carried out in order to gain a better understanding of the different collapse modes of thin-walled square and cylindrical tubes. The ability of numerical models to predict the failure modes and forces associated with the collapse of the tubes accurately has meant that extensive time and expense required for experimental methods can be eliminated.